FACTORS ASSOCIATED WITH EXCLUSIVE BREASTFEEDING AMONG MOTHER IN BANJARMASIN, SOUTH KALIMANTAN - Aprizal Satria Hanafi; Ema Novita Deniati (Faculty of Public Health, Sriwijaya University, 2018)
Background: Exclusive breastfeeding is recommended food for infants until the age of 6 months. After 6 months years old a complementary food is recommended until 2 years of age. However, percent of mothers practicing exclusive breastfeeding is still low. This study aimed to determine factors associated with exclusive breastfeeding among mothers in Banjarmasin, South Kalimantan. Method: This was a case-control study conducted in Banjarmasin, South Kalimantan from June to December 2016. A sample of 258 lactating mothers, consisting of 136 mothers who exclusively breastfed (control group) and 122 mothers who did not exclusively breastfeed (case group), were selected for this study by purposive sampling. Data were collected by pre-tested questionnaire and interview. Data were analyzed by logistic regression. Results: Low mother education (OR=1.34; 95% CI=1.18-1.82), low mother knowledge (OR=2.24; 95% CI=1.69-2.42), poor mother health condition (OR=1.34, 95% CI=0.08-3.93), and low family support (OR=2.06; 95% CI=0.02-8.93) were associated with decreased chance of exclusive breastfeeding. Mother age 20-29 years (OR=2.82; 95% CI=0.18-6.74) and housewife status (OR=2.54; 95% CI=1.00-8.29) were associated with increased chance of exclusive breastfeeding. Interview result showed that lack of mother knowledge on the utility of exclusive breastfeeding was a strong predictor for not practicing exclusive breastfeeding. Most of the mothers interviewed believed that providing food in addition to breastmilk could accelerate the growth of their children. Conclusion: Lack of knowledge about benefits of exclusive breastfeeding was the dominant predictor factor and potentially inhibit exclusive breastfeeding. Promotion of exclusive breastfeeding should be improved by health workers to mothers so that they can understand the benefits of exclusive breastfeeding in children.